Are running and swimming two independently evolved behaviors? A study of world-class triathletes - Papadimitriou, I.; Papadopoulos, C. (New Studies in Athletics, 2007)
This study aimed to explore covariation among triathletes who train to perform optimally in two different environments (land and water) and three different disciplines (running, swimming and biking. The best 190 performances in the 2002 Ironman Triathlon were intercorrelated in order to understand how performance in one discipline is related to performance in the others. A strong positive correlation (P = 0.0002) was found not only between running and biking but also between biking and swimming. Interestingly. no correlation between running and swimming was found. Thus, running performance does not appear to have predictive value for swimming performance and vice versa. Although not direct evidence of a performance trade-off, these findings may be evidence that running and swimming are independently-evolved behaviours. It is possible that some physiological characteristics have a positive effect on both running and swimming performance, but others characteristics, which may have evolved independently for optimising performance in one activity or the other, may show a trade-off effect.